Predictors of schoolteachers' intention to report suspected child abuse and neglect cases in Oman: A national study - Zeinab Al Azri; Wafa A.L. Jabri; Iman Al Hashmi; Asia Alnaamani; Omar Al Zaabi (Acta Psychologica)
Background: Although schoolteachers in Oman are legally mandated to report all child abuse cases, they often show reluctance to do so. This hesitancy can deprive abuse victims of necessary help, potentially leaving them to endure long-term consequences. Oman's efforts to combat child abuse and neglect align with international best practices. However, these measures might be ineffective without considering their applicability to a collective society like Oman. Aim: This study examined the predictors of schoolteachers' intention to report child abuse and neglect in Oman, considering their demographic and professional characteristics, attitudes toward reporting, subjective norms, and perceived behavioral control. Methods: This cross-sectional study was conducted across 280 cycle one-basic education public schools in Oman. The Intention to Report Child Abuse Tool (IRCAT) was used to measure intention to report, perceived behavioral control, attitudes toward reporting, and subjective norms. A total of 653 schoolteachers were recruited using a convenience sampling technique. Results: The mean total score for the intention to report subscale was 24.24 out of 36 (SD = 7.44), indicating an acceptable level. A stepwise regression analysis yielded one significant model (F (1, 651) = 112.23, p = 0.001), which included perceived behavioral control, with an adjusted R2 of 0.146. Conclusion: This study's findings highlight influential variables that can guide future interventions. These results provide stakeholders with directions for designing culturally sensitive interventions to enhance the reporting of suspected child abuse cases in Oman.